Unveiling new sequestrate Cortinarius species from northern Patagonian Nothofagaceae forests based on molecular and morphological data. (2nd January 2019) - Pastor, Nicolás; Chiapella, Jorge; Kuhar, Francisco; Mujic, Alija Bajro; Crespo, Esteban M.; Nouhra, Eduardo R.
ABSTRACT: Because of systematic sampling campaigns in the northern Patagonian Nothofagaceae forests of Argentina, several specimens of sequestrate fungi were collected. Some of those collections showed phylogenetic affinities and morphological similarities to members of the formerly recognized sequestrate genus Thaxterogaster, currently a synonym of Cortinarius on the basis of molecular data. Comparisons of macro- and micromorphological features and sequences of nuc rDNA internal transcribed spacer (ITS) regions have revealed that these collections belong to formerly undescribed species. The sequences of the four new taxa presented here, Cortinarius flavopurpureus, C. translucidus, C. nahuelhuapensis, and C. infrequens, were combined into a data set including additional sequences generated from herbarium collections and retrieved from public gene databases and analyzed by maximum likelihood and Bayesian inference methods. The four new species were resolved as distinct clades with strong support; at the same time, they showed unique morphological characteristics (hypogeous to subhypogeous habit, complete gasteromycetation, and spore shape and ornamentation) that separate them from previously described Cortinarius species. In addition, several undescribed and/or not previously sequenced species from these forests were detected through phylogenetic analysis of ectomycorrhizal root tip sequences. A key of characters to identify the sequestrate Cortinarius from Patagonia is provided.